A fabrication process to make CNT/EP composite strain sensors. (March 2018) - Kaiyan, Huang; Weifeng, Yuan; Shuying, Tong; Haidong, Liu
Carbon nanotube (CNT)/epoxy resin (EP) conductive composite can be obtained by solidifying the mixture of CNT and EP at specific temperature. The conductivity of the CNT/EP composite rises as the CNT content increases. It has been proven that the electrical resistance of a CNT/EP film varies when it experiences tension or compression. Therefore, the current research focuses on the design of strain sensors, based on the piezoresistivity of CNT/EP composite. In this article, an efficient method used to fabricate CNT/EP sensors is introduced in detail. One main novelty of the present method is that it provides an easy process to install metal electrodes for each piece of CNT/EP film. Another importance of the method is that it tackles the obstacles on the way to bulk production. A cantilever beam system was used to test the sensors fabricated through the self-developed process. The experimental results show that the sensors have consistent properties, and their gauge factors are much higher than that of typical foil strain gauges.